A contemporary perspective on the disaster management cycle. Issue 4 (28th May 2020) - Sawalha, Ihab Hanna
Abstract : Purpose: This study aims to examine the traditional disaster management cycle; discussing the significance of incorporating contemporary management concepts into the disaster management cycle; and proposing a conceptual model that reflects contemporary management insight for the disaster management cycle. Design/methodology/approach: A literature review was made to discuss the significance of moving towards a more contemporary view to the disaster management cycle that brings more value to the final outcomes of the disaster management process. A conceptual model was then proposed to reflect a more contemporary view to the disaster management cycle. The current COVID-19 pandemic has also been addressed explicitly throughout the paper as a case that reflects the necessity of embracing contemporary insight and practise in the traditional disaster management cycle. Findings: The literature indicates that people worldwide, as well as academics still rely heavily on the traditional disaster management lifecycle to manage disasters and major incidents which consists of four main stages; preparedness, mitigation, response and recovery unrecognizing that each and every disaster is a unique incident itself and that it should be treated differently. Contemporary management thought and insight is still lacking in the study of disaster and emergency management. Practical implications: This research offers a contemporary view to the traditional disaster management cycle in which recent concepts of management are used to better cope with the uniqueness of the different major incidents. This view fosters wider involvement of individuals and the general public in the disaster management process and highlights elements of creativity and modernity. The current COVID-19 pandemic, despite the many adverse consequences associated with it, has contributed constructively to the ways the traditional disaster management cycle is being implemented and practised worldwide. Originality/value: This research is expected to be of a substantial value for those interested in improving performance during the various stages of the disaster management process, as well as those interested in improving organizational, social and national resilience. The traditional disaster management cycle tends to be procedural and therefore needs to embrace contemporary management thought and more value-based approaches.